El derecho de la víctima a comparecer en todas las etapas del proceso penal sin el requisito de la acusación particular. - Portilla, Pablo (2022)
The importance of the subject lies in verifying through a thorough investigation, if in criminal proceedings in the Ibarra canton, the victims of crimes are allowed to participate in hearings at any stage of the process, without the formal requirement that they have presented private prosecution, so that they can exercise their right to defense through practice of evidence, as determined by article 432 of the Comprehensive Organic Criminal Code, and the article 76 numeral 7 of the Constitution of the Republic of Ecuador. The prevent the crime victims intervene in hearings would violate the guarantees of due process constitutionally enshrined. Through this investigative work it will be possible to have a clear vision regarding whether the Judges of Criminal Guarantees and Judges of the Criminal Court of the Ibarra canton respect the regulations in force in the Ecuadorian legal system, which grants victims of crimes in criminal proceedings, the power to intervene in all hearings at any stage of the process, allowing them to participate in hearings, present their arguments of orally, practice their evidence and contradict those presented by the opposing party, with the purpose that the right to defense of the victims is not violated guaranteed constitutionally.